Jane S. Richardson Oral History Interview, 2007 - Richardson, Jane S. (2007)
Jane S. Richardson discusses her background; her interest in astronomy; her interest in philosophy; working in the same lab where her husband, David Richardson, was getting his PhD; in 1969, the laboratory solving the structure of the Staphylococcal nuclease, the tenth protein structure to be determined; her enjoyment of being unknown; working as a technician in the laboratory; what the structure of a protein might tell about that protein; solving the crystal structure of copper/zinc superoxide dismutase at Duke; learning about the geometry of the active site of this enzyme; the significance of knowing the structure of proteins; X-ray crystallography as the technique used then and still used to solve protein structures; the current worldwide Protein Data Bank, which stores about fifty thousand protein structures; her work as a technician; working on computer models of proteins as early as 1960s; current work of the Richardson lab: building tools for determining and analyzing RNA structure; all-atom contact analysis; other people at Duke currently actively working on protein structure, although not the Richardson lab; Jane Richardson being most noted for ribbon drawings of proteins; ribbon drawings outlining the schematics of all known protein structures in 1980; she and her husband not being able to be in the same department due to nepotism rule at the time; creating a uniform set of conventions for the protein ribbon drawings; the freedom to do this work because she was "invisible"; Duke giving her tenure when she became a member of the National Academy of Sciences; common structures depicted in the ribbon drawings; subjectivity of representing protein structures because she outlined the conventions of the drawings; the ubiquitous nature of the ribbon drawings due to computer graphics; current use of the same conventions; her original method of drawing on top of a computer printout of a very simplified protein structure; the laboratory's invention of Kinemages, one of the first molecular graphics systems available on personal computers; the current size of the laboratory; Duke in the 1970s; Dr. Robert Hill; women as being "on the edges" of the department; her own unusual career track; not getting a PhD; this fact embarrassing the university once she became well-known; receiving a MacArthur Fellowship because of the ribbon drawings; her own circuitous route as being useful; the collaborative nature of her work with her husband; the difficulty in current scientific culture of collaborating, since the tenure emphasis is on receiving credit for something; change in the nepotism rule; pairs of scientists; the connectivity of the current field due to computers; pressure as one result of connectivity; and her enjoyment of having many female colleagues currently. The transcription of this interview was made possible by a grant from the Josiah Charles Trent Memorial Foundation.